Cement wastes as transesterification catalysts for the production of biodiesel from Karanja oil. (10th May 2018) - Kumar, Dipesh; Singh, Bhaskar; Banerjee, Ayan; Chatterjee, Sandeep
Abstract: Construction and demolition waste materials such as concrete and mortar have limited reuse and recycling, and as a result, are accumulating in landfills. In this work, the utility of concrete and mortar waste materials as transesterification catalysts for the production of biodiesel from non-edible Karanja oil has been investigated. Locally collected concrete and mortar were washed thoroughly, dried, ground, sieved and calcined at 850 °C for 3 h before their use as transesterification catalysts. These materials were characterised by using X-ray diffraction, Fourier transform infrared spectroscopy and Hammett basicity indicator methods. The basic strength of the calcined materials (15.0 >  H_  ≥ 10.1) was found to be higher than the uncalcined materials. The catalytic activity of cementitious waste materials has been compared with that of cement and commercial grade CaO. Among all cementitious materials tested, cement was found to be the most efficient (76 ± 0.3%) in the transesterification of Karanja oil to biodiesel. The experimental results were used to conduct an economic analysis of a 50 kt biodiesel production facility using cement as a heterogeneous catalyst. The final manufacturing cost of biodiesel was estimated to be $1.23 kg −1 . Highlights: Cement wastes were employed as a transesterification catalyst. Calcination of cement wastes led to enhanced basic strength. Results substantiate the basic nature of cementitious materials. Cement was found to be most effective catalyst (76 ± 0.3% conversion). The unit production cost of biodiesel was estimated to be $ 1.23 kg −1 .